The Influence of the Level of Knowledge of the Importance of Digital Business on the Interest of Prospective Students to Enroll in the Digital Business Study Program of Wiraraja University - Moh. Baqir Ainun; Ahmad Ghufrony; Fathorrahman Fathorrahman; Stevan Ariputra Harmanto; Diah Anggreini Pitaloka (Journal of Social Research, 2023)
The purpose of this study is to determine the influence of the Level of Knowledge of the Importance of Digital Business on the Interest of Prospective Students enrolling in the Digital Business Study Program of Wiraraja University. In addition, this study also tested the moderation effect of Knowledge Level on the Digital Business Study Program of Wiraraja University. This study used questionnaires distributed to Menenga Atas School Students and equivalent in Sumenep Regency. The number of respondents was 257 out of 7 high schools in Sumenep. Data analysis was performed using SmartPLS Structural Equation Modelling (SEM) at a significant rate of 5%. The results showed that the level of knowledge of the importance of digital business has a significant positive effect on the interest of prospective students to enroll in the Digital Business study program of Wiraraja University. In addition, the Level of Knowledge about the Digital Business Study Program of Wiraraja University is also proven to have a moderation effect. The first implication of this research is that universities, especially Wiraraja University, must socialize the importance of digital business in the digital era to prospective new students and make it a reason to invite prospective new students to enroll in the Digital Business study program. The second implication is that universities, especially Wiraraja University, must promote that Wiraraja University has opened a Digital Business study program that promises competent graduates in Digital Business.